Meningkatan Kemampuan Berpikir Kritis Siswa Pada Pendidikan Agama Katolik dan Budi Pekerti Kelas IX Dengan Model PBL SMPN 3 Pegagan Hilir - Anwar Siburian (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve students' critical thinking skills in the subject of Catholic Religious Education and Character through the implementation of the Problem-Based Learning (PBL) model. The background of this research is based on the low cognitive learning outcomes of students, particularly in critical thinking and problem-solving skills. The research was conducted at SMP Negeri 3 Pegagan Hilir with a sample of 12 students from class IX-A. The research method used was Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of the stages of planning, implementation, observation, and reflection. The instruments used included observation sheets and evaluation tests. The research results showed an increase in students' critical thinking skills in the second cycle compared to the first cycle. The average score of students' critical thinking skills increased from 70 in the first cycle to 88 in the second cycle, with a learning mastery rate of 90%. The implementation of the PBL model proved effective in enhancing students' participation in group discussions, critical thinking skills, and learning motivation. This model also helped students connect the concepts learned with real-life situations, thereby improving their understanding and learning outcomes